Degradable packaging material and preparation method thereof
Through hot rolling preparation of modified polylactic acid, modified eloite nanotubes and cellulose, the shortcomings of existing packaging materials in terms of mechanical properties, antibacterial properties and degradation rate are solved, and the preparation of high-performance degradable packaging materials is achieved. .
Patent Information
- Application Number
- CN202411535933.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing degradable packaging materials have shortcomings in terms of mechanical properties, antibacterial properties and degradation rates, and it is difficult to meet the needs of high-performance packaging materials.
By mixing hot rolling of modified polylactic acid, modified elolite nanotubes and cellulose, a degradable packaging material with improved mechanical properties, antibacterial properties and accelerated degradation rate is formed.
It has achieved improvement in mechanical properties, enhanced antibacterial properties and improved degradation rate of packaging materials, meeting the market demand for high-performance degradable packaging materials.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of packaging materials, in particular to a degradable packaging material and a preparation method thereof. Background Art
[0002] Packaging materials are widely used in the fields of food, medicine, electronic products and daily necessities for protection, storage and transportation. However, traditional packaging materials are often difficult to degrade, which can pollute the environment and cause ecological problems. Therefore, there is an urgent need to develop degradable packaging materials to reduce the environmental burden.
[0003] At present, degradable packaging materials mainly include biodegradable materials, photodegradable materials, etc. Common biodegradable materials include polylactic acid, poly 3-hydroxyalkanoate, etc. Photodegradable materials are usually achieved by introducing photosensitive groups or photoinitiators into traditional plastics, and they can be rapidly degraded in ultraviolet light environments; although biodegradable materials such as polylactic acid have good biodegradability and processability, they are inherently brittle, have poor heat resistance, and have a single function. In order to broaden the scope of use of polylactic acid and improve its comprehensive performance, polylactic acid can be modified to enhance its mechanical properties, giving polylactic acid antibacterial properties and flame retardant properties, which can broaden the application of polylactic acid materials in food packaging and electronic packaging, thereby better meeting the market demand for high-performance degradable packaging materials. At the same time, how to combine photodegradation and biodegradation to accelerate the degradation rate of packaging materials is one of the important directions in the current field of degradable materials. Summary of the invention
[0004] The object of the present invention is to provide a degradable packaging material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A degradable packaging material is prepared by mixing and hot-rolling modified polylactic acid, modified halloysite nanotubes and cellulose.
[0007] The modified polylactic acid is prepared by reacting terminal hydroxyl polylactic acid with 3-chloropropionyl chloride, then with 1,2-bis(vinylphosphine)ethane, and finally with 4-mercaptophenylboronic acid.
[0008] The modified halloysite nanotube is prepared by reacting the halloysite nanotube pretreated with trimethoxy(2-phenylethyl)silane and 3,4-dihydroxybenzoic acid.
[0009] A method for preparing a degradable packaging material comprises the following steps:
[0010] (1) Under nitrogen protection, hydroxy-terminated polylactic acid and tetrahydrofuran are mixed in a mass ratio of 1:(20-30), and triethylamine in an amount of 4 times the mass of the hydroxy-terminated polylactic acid is added at 0°C, and then a 3-chloropropionyl chloride solution in an amount of 20 times the mass of the hydroxy-terminated polylactic acid is added dropwise at a rate of 1 mL / min. After the addition is completed, the mixture is stirred for 3-4 hours, the mixture is heated to room temperature, the reaction is continued for 12 hours, and the mixture is centrifuged at 5000 r / min for 30 minutes. The supernatant is taken, and the supernatant is added to n-hexane in an amount of 5 times the volume of tetrahydrofuran at -4°C for precipitation, and the mixture is filtered and vacuum dried at 40°C for 24 hours to obtain chlorine-terminated polylactic acid;
[0011] (2) trivinyl phosphine and tetrahydrofuran are mixed in a mass ratio of 1:(5-6), stirred for 30-40 min under nitrogen protection, lithium in an amount of 0.05-0.07 times the mass of trivinyl phosphine is added, stirring is continued for 4-5 h, the temperature is lowered to 0° C., a tert-butyl chloride solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, after the addition is completed, the temperature is raised to room temperature, the mixture is reacted at room temperature for 2 h, and a dichloroethane solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, the reaction is continued for 1 h after the addition is completed, and after the reaction is completed, the tetrahydrofuran is removed by vacuum rotary evaporation to obtain 1,2-bis(vinylphosphine)ethane;
[0012] (3) Chloro-terminated polylactic acid, 1,2-bis(vinylphosphine)ethane, potassium iodide, and dimethyl sulfoxide are mixed in a mass ratio of 1:(7-9):(0.3-0.5):(20-30), reacted at 70-80° C. for 8-10 h, and after the reaction, pure water 4 times the volume of dimethyl sulfoxide is added for precipitation, filtered, and vacuum dried at 40° C. for 24 h to obtain pre-modified polylactic acid;
[0013] (4) Azobisisobutyronitrile, 4-mercaptophenylboric acid, and dimethyl sulfoxide are mixed in a mass ratio of 1:(2-3):(10-12), and pre-modified polylactic acid is added in an amount 2-3 times the mass of azobisisobutyronitrile. Under nitrogen protection, the temperature is raised to 65-70° C. for reaction for 24 h. After cooling to room temperature, pure water 4 times the volume of dimethyl sulfoxide is added for precipitation. The mixture is filtered and vacuum dried at 40° C. for 24 h to obtain modified polylactic acid.
[0014] (5) 3,4-dihydroxybenzoic acid, pretreated halloysite nanotubes, anhydrous zinc chloride, phosphorus oxychloride, and sulfolane are mixed in a mass ratio of 1:(0.3-0.5):(1.3-1.5):(1.1-1.2):(20-30), heated to 65-70° C., reacted for 2-3 hours, added with pure water of an equal volume to the sulfolane, stirred for 5-10 minutes, continued to add pure water 30 times the volume of the sulfolane, stirred for 5-10 minutes, allowed to stand for 40 minutes, filtered, washed with pure water 3 times, and vacuum dried for 12 hours to obtain modified halloysite nanotubes;
[0015] (6) The modified polylactic acid, the modified halloysite nanotubes and the cellulose were mixed, kneaded on an internal mixer at a temperature of 170° C. and a rotation speed of 30 rpm for 5-10 min, and then hot-rolled on a press at a pressure of 10 MPa and a temperature of 180° C. for 10 min to obtain a degradable packaging material.
[0016] As an optimization, the preparation method of the terminal hydroxyl polylactic acid in step (1) is as follows: lactic acid and 1,4-butanediol are mixed at a mass ratio of 1:0.001 at 0.096 MPa, heated to 125°C, distilled for 3 hours, 0.8% of the mass of lactic acid by stannous octoate is added, and the temperature is raised to 170°C, melt polycondensed for 9 hours, after the reaction is completed, 10 times the mass of lactic acid by chloroform is added and stirred for 10 minutes, and then 4 times the mass of chloroform by anhydrous ethanol is added for precipitation, filtered and vacuum dried at 40°C for 24 hours to obtain the terminal hydroxyl polylactic acid.
[0017] As an optimization, the 3-chloropropionyl chloride solution in step (1) is prepared by mixing 3-chloropropionyl chloride and tetrahydrofuran in a mass ratio of 1:5.
[0018] As an optimization, the tert-butyl chloride solution in step (2) is a mixture of tert-butyl chloride and tetrahydrofuran in a mass ratio of (0.5-0.7):20; the dichloroethane solution is a mixture of dichloroethane and tetrahydrofuran in a mass ratio of (0.2-0.3):20.
[0019] As an optimization, the preparation method of the pretreated halloysite nanotubes in step (5) is: trimethoxy (2-phenylethyl) silane and pure water are mixed in a mass ratio of 1:50, the pH is adjusted to 4.5-5.5 with acetic acid, and after stirring at 60°C for 15 minutes, 5 times the mass of halloysite nanotubes of trimethoxy (2-phenylethyl) silane are added, stirring is continued for 2 hours, filtering and washing with anhydrous ethanol for 4 times, and drying at 100°C to obtain pretreated halloysite nanotubes.
[0020] As an optimization, the mass ratio of the modified polylactic acid, modified halloysite nanotubes and cellulose in step (6) is 1:(0.03-0.05):(0.2-0.3); the cellulose is corn straw cellulose powder with a particle size of 100 mesh, purchased from Jinan Shengquan Group Co., Ltd.
[0021] As an optimization, the lactic acid is L-lactic acid with a concentration of 88% and an optical rotation of ≥97%.
[0022] As an optimization, the halloysite nanotubes have a diameter of 30-50 nm and a length of 100-500 nm, and were purchased from Hebei Qingtai Minerals Co., Ltd.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0024] When preparing the degradable packaging material, the present invention comprises the following steps: firstly, terminal hydroxyl polylactic acid is reacted with 3-chloropropionyl chloride, then reacted with 1,2-bis(vinylphosphine)ethane, and finally reacted with 4-mercaptophenylboric acid to obtain modified polylactic acid; secondly, halloysite nanotubes pretreated with trimethoxy(2-phenylethyl)silane are reacted with 3,4-dihydroxybenzoic acid to obtain modified halloysite nanotubes; finally, the modified polylactic acid, the modified halloysite nanotubes and cellulose are mixed and hot-rolled to obtain the degradable packaging material.
[0025] First, the hydroxy-terminated polylactic acid is reacted with 3-chloropropionyl chloride, then reacted with 1,2-bis(vinylphosphine)ethane, and finally reacted with 4-mercaptophenylboronic acid to obtain modified polylactic acid; the hydroxy-terminated polylactic acid is reacted with the acyl chloride on 3-chloropropionyl chloride to obtain chlorine-terminated polylactic acid, and the chlorine-terminated polylactic acid is reacted with 1,2-bis(vinylphosphine)ethane to form a quaternary phosphonium salt to extend the chain of polylactic acid, and the chain extension can quickly and effectively increase the chain length of polylactic acid, improve the relative molecular weight of polylactic acid, stabilize the molecular chain structure, and improve its toughness and mechanical strength. The formation of the quaternary phosphonium salt can give the packaging material good antibacterial properties, and 1,2-bis(vinylphosphine)ethane can also introduce phosphorus elements with flame retardant properties into the polylactic acid to give the material good flame retardant properties, and can also introduce double bonds, and the double bonds are reacted with the thiol group of 4-mercaptophenylboronic acid to further introduce phenylboronic acid structure into the side chain of polylactic acid;
[0026] Secondly, the halloysite nanotubes pretreated with trimethoxy (2-phenylethyl) silane are reacted with 3,4-dihydroxybenzoic acid to obtain modified halloysite nanotubes. The halloysite nanotubes as an inorganic filler can enhance the mechanical properties of polylactic acid. The silane coupling agent trimethoxy (2-phenylethyl) silane is grafted on the surface of the halloysite nanotubes through the silanol group after hydrolysis, so that the surface of the halloysite nanotubes has phenyl groups. The phenyl groups react with 3,4-dihydroxybenzoic acid to generate a benzophenone structure. The carbonyl group contained in the benzophenone structure is a type of photosensitive group. After absorbing ultraviolet rays under sunlight, free radicals are generated, which promote the oxidation of the polylactic acid molecular chain, generate fractures, and degrade into low molecular weight compounds, thereby accelerating the degradation process of the polylactic acid and improving the degradation rate.
[0027] Finally, modified polylactic acid, modified halloysite nanotubes and cellulose are mixed and hot-rolled to obtain a degradable packaging material. The phenylboric acid structure of the polylactic acid side chain, the phenolic hydroxyl structure on the surface of the modified halloysite nanotubes, and the polyphenolic hydroxyl structure on the cellulose can be cross-linked with phenylboric acid at high temperature to form a reversible borate ester structure. The formation of a cross-linked network can enhance the mechanical properties of the modified polylactic acid. At the same time, the ability of the borate ester structure to be alcoholyzed or enzymatically hydrolyzed under mild conditions can further improve the degradation rate of polylactic acid. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] The cellulose used in the following examples and comparative examples is corn straw cellulose powder with a particle size of 100 mesh, purchased from Jinan Shengquan Group Co., Ltd.; the lactic acid used is L-lactic acid with a concentration of 88% and an optical rotation of ≥97%; the halloysite nanotubes used have a diameter of 30-50 nm and a length of 100-500 nm, purchased from Hebei Qingtai Minerals Co., Ltd.; the 3-chloropropionyl chloride solution used is prepared by mixing 3-chloropropionyl chloride and tetrahydrofuran in a mass ratio of 1:40.
[0030] Embodiment 1:
[0031] A method for preparing a degradable packaging material, the method for preparing the degradable packaging material comprising the following preparation steps:
[0032] (1) Lactic acid and 1,4-butanediol were mixed at a mass ratio of 1:0.001 under 0.096 MPa, heated to 125° C., distilled for 3 h, added with 0.8% of the mass of lactic acid stannous octoate, heated to 170° C., melt polycondensed for 9 h, and after the reaction was completed, added 10 times the mass of lactic acid chloroform and stirred for 10 min, then added 4 times the mass of chloroform anhydrous ethanol for precipitation, filtered and vacuum dried at 40° C. for 24 h to obtain hydroxyl-terminated polylactic acid; under nitrogen protection, hydroxyl-terminated polylactic acid and tetrahydrofuran were mixed. The mixture was mixed with tetrahydrofuran and 1,2-tetrahydrofuran in a mass ratio of 1:2, and triethylamine 4 times the mass of the end-hydroxyl polylactic acid was added at 0°C, and then 3-chloropropionyl chloride solution 20 times the mass of the end-hydroxyl polylactic acid was added dropwise at a dropping speed of 1 mL / min. After the addition was completed, the mixture was stirred for 4 hours, the temperature was raised to room temperature, and the reaction was continued for 12 hours. The mixture was centrifuged at 5000 r / min for 30 minutes, the supernatant was taken, and the supernatant was added to n-hexane 5 times the volume of tetrahydrofuran at -4°C for precipitation, and the mixture was filtered and vacuum dried at 40°C for 24 hours to obtain chlorine-terminated polylactic acid;
[0033] (2) trivinyl phosphine and tetrahydrofuran are mixed in a mass ratio of 1:5, stirred for 40 minutes under nitrogen protection, lithium is added in an amount of 0.05 times the mass of trivinyl phosphine, stirring is continued for 5 hours, the temperature is lowered to 0°C, tert-butyl chloride and tetrahydrofuran are mixed in a mass ratio of 0.5:20 to obtain a tert-butyl chloride solution; the tert-butyl chloride solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, after the addition is completed, the temperature is raised to room temperature, and the mixture is reacted at room temperature for 2 hours, dichloroethane and tetrahydrofuran are mixed in a mass ratio of 0.2:20 to obtain a dichloroethane solution, the dichloroethane solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, the reaction is continued for 1 hour after the addition is completed, and after the reaction is completed, the tetrahydrofuran is removed by vacuum rotary evaporation to obtain 1,2-bis(vinylphosphine)ethane;
[0034] (3) Chloro-terminated polylactic acid, 1,2-bis(vinylphosphine)ethane, potassium iodide, and dimethyl sulfoxide were mixed in a mass ratio of 1:7:0.3:20, reacted at 80°C for 10 hours, and after the reaction, pure water 4 times the volume of dimethyl sulfoxide was added for precipitation, filtered, and vacuum dried at 40°C for 24 hours to obtain pre-modified polylactic acid;
[0035] (4) Azobisisobutyronitrile, 4-mercaptophenylboric acid, and dimethyl sulfoxide were mixed in a mass ratio of 1:2:10, and pre-modified polylactic acid with a mass twice that of azobisisobutyronitrile was added. Under nitrogen protection, the temperature was raised to 70° C. for reaction for 24 h. After cooling to room temperature, pure water with a volume of 4 times that of dimethyl sulfoxide was added for precipitation. The mixture was filtered and vacuum dried at 40° C. for 24 h to obtain modified polylactic acid.
[0036] (5) Trimethoxy (2-phenylethyl) silane and pure water were mixed in a mass ratio of 1:50, and the pH was adjusted to 5.5 with acetic acid. After stirring at 60°C for 15 minutes, 5 times the mass of trimethoxy (2-phenylethyl) silane was added to the halloysite nanotubes, and the stirring was continued for 2 hours. The mixture was filtered and washed with anhydrous ethanol for 4 times, and dried at 100°C to obtain pretreated halloysite nanotubes; 3,4-dihydroxybenzoic acid, pretreated halloysite nanotubes, anhydrous zinc chloride, phosphorus oxychloride, and cyclopentane were mixed in a mass ratio of 1:0.3:1.3:1.1:20, heated to 70°C, reacted for 3 hours, and pure water of an equal volume to cyclopentane was added and stirred for 10 minutes. Pure water of 30 times the volume of cyclopentane was continued to be added, stirred for 10 minutes, and then allowed to stand for 40 minutes. The mixture was filtered and washed with pure water for 3 times, and vacuum dried for 12 hours to obtain modified halloysite nanotubes;
[0037] (6) Weighing modified polylactic acid, modified halloysite nanotubes, and cellulose in a mass ratio of 1:0.03:0.2; mixing the modified polylactic acid, modified halloysite nanotubes, and cellulose, kneading them on an internal mixer at a temperature of 170° C. and a rotation speed of 30 rpm for 10 min, and then hot-rolling them on a press at a pressure of 10 MPa and a temperature of 180° C. for 10 min to obtain a biodegradable packaging material.
[0038] Embodiment 2:
[0039] A method for preparing a degradable packaging material, the method for preparing the degradable packaging material comprising the following preparation steps:
[0040] (1) Lactic acid and 1,4-butanediol were mixed at a mass ratio of 1:0.001 under 0.096 MPa, heated to 125° C., distilled for 3 h, added with 0.8% of the mass of lactic acid stannous octoate, heated to 170° C., melt polycondensed for 9 h, and after the reaction was completed, added 10 times the mass of lactic acid chloroform and stirred for 10 min, then added 4 times the mass of chloroform anhydrous ethanol for precipitation, filtered and vacuum dried at 40° C. for 24 h to obtain hydroxyl-terminated polylactic acid; under nitrogen protection, hydroxyl-terminated polylactic acid and tetrahydrofuran were mixed. Mix them in a mass ratio of 1:25, add triethylamine 4 times the mass of the terminal hydroxyl polylactic acid at 0°C, and then drop 3-chloropropionyl chloride solution 20 times the mass of the terminal hydroxyl polylactic acid at a dropping speed of 1 mL / min. Stir for 3.5 hours after the addition is completed, warm to room temperature, continue to react for 12 hours, centrifuge at 5000 r / min for 30 minutes, take the supernatant, add the supernatant to n-hexane 5 times the volume of tetrahydrofuran at -4°C for precipitation, filter and vacuum dry at 40°C for 24 hours to obtain terminal hydroxyl polylactic acid;
[0041] (2) trivinyl phosphine and tetrahydrofuran are mixed at a mass ratio of 1:5.5, stirred for 35 minutes under nitrogen protection, lithium is added in an amount of 0.06 times the mass of trivinyl phosphine, stirring is continued for 4.5 hours, the temperature is lowered to 0°C, tert-butyl chloride and tetrahydrofuran are mixed in a mass ratio of 0.6:20 to obtain a tert-butyl chloride solution; the tert-butyl chloride solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, after the addition is completed, the temperature is raised to room temperature, and the mixture is reacted at room temperature for 2 hours, dichloroethane and tetrahydrofuran are mixed in a mass ratio of 0.25:20 to obtain a dichloroethane solution, the dichloroethane solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, the reaction is continued for 1 hour after the addition is completed, and after the reaction is completed, the tetrahydrofuran is removed by vacuum rotary evaporation to obtain 1,2-bis(vinylphosphine)ethane;
[0042] (3) Chloro-terminated polylactic acid, 1,2-bis(vinylphosphine)ethane, potassium iodide, and dimethyl sulfoxide were mixed in a mass ratio of 1:8:0.4:25, reacted at 75°C for 9 hours, and after the reaction, pure water 4 times the volume of dimethyl sulfoxide was added for precipitation, filtered, and vacuum dried at 40°C for 24 hours to obtain pre-modified polylactic acid;
[0043] (4) Azobisisobutyronitrile, 4-mercaptophenylboric acid, and dimethyl sulfoxide were mixed in a mass ratio of 1:2.5:11, and 2.5 times the mass of azobisisobutyronitrile was added to pre-modified polylactic acid, and the mixture was heated to 68°C for reaction for 24 hours under nitrogen protection. After cooling to room temperature, pure water 4 times the volume of dimethyl sulfoxide was added for precipitation, and the mixture was filtered and vacuum dried at 40°C for 24 hours to obtain modified polylactic acid;
[0044] (5) Trimethoxy (2-phenylethyl) silane and pure water were mixed in a mass ratio of 1:50, and the pH was adjusted to 5.0 with acetic acid. After stirring at 60°C for 15 minutes, 5 times the mass of trimethoxy (2-phenylethyl) silane was added to the halloysite nanotubes, and the stirring was continued for 2 hours. The mixture was filtered and washed with anhydrous ethanol for 4 times, and dried at 100°C to obtain pretreated halloysite nanotubes; 3,4-dihydroxybenzoic acid, pretreated halloysite nanotubes, anhydrous zinc chloride, phosphorus oxychloride, and cyclopentane were mixed in a mass ratio of 1:0.4:1.4:1.15:25, heated to 68°C, reacted for 2.5 hours, and pure water of an equal volume to cyclopentane was added and stirred for 7 minutes. Pure water of 30 times the volume of cyclopentane was continued to be added, stirred for 7 minutes, and then allowed to stand for 40 minutes. The mixture was filtered and washed with pure water for 3 times, and vacuum dried for 12 hours to obtain modified halloysite nanotubes;
[0045] (6) Weighing modified polylactic acid, modified halloysite nanotubes, and cellulose in a mass ratio of 1:0.04:0.25; mixing the modified polylactic acid, modified halloysite nanotubes, and cellulose, kneading them on an internal mixer at a temperature of 170° C. and a rotation speed of 30 rpm for 7 min, and then hot-rolling them on a press at a pressure of 10 MPa and a temperature of 180° C. for 10 min to obtain a biodegradable packaging material.
[0046] Embodiment 3:
[0047] A method for preparing a degradable packaging material, the method for preparing the degradable packaging material comprising the following preparation steps:
[0048] (1) Lactic acid and 1,4-butanediol were mixed at a mass ratio of 1:0.001 under 0.096 MPa, heated to 125° C., distilled for 3 h, added with 0.8% of the mass of lactic acid stannous octoate, heated to 170° C., melt polycondensed for 9 h, and after the reaction was completed, added 10 times the mass of lactic acid chloroform and stirred for 10 min, then added 4 times the mass of chloroform anhydrous ethanol for precipitation, filtered and vacuum dried at 40° C. for 24 h to obtain hydroxyl-terminated polylactic acid; under nitrogen protection, hydroxyl-terminated polylactic acid and tetrahydrofuran were mixed. The mixture was stirred for 3 h after the addition was completed, and the mixture was heated to room temperature, and the reaction was continued for 12 h. The mixture was centrifuged at 5000 r / min for 30 min, and the supernatant was taken. The supernatant was added into n-hexane 5 times the volume of tetrahydrofuran at -4 °C for precipitation, and the mixture was filtered and dried in vacuum at 40 °C for 24 h to obtain chloro-terminated polylactic acid.
[0049] (2) trivinyl phosphine and tetrahydrofuran are mixed in a mass ratio of 1:6, stirred for 30 minutes under nitrogen protection, lithium is added in an amount of 0.07 times the mass of trivinyl phosphine, stirring is continued for 4 hours, the temperature is lowered to 0°C, tert-butyl chloride and tetrahydrofuran are mixed in a mass ratio of 0.7:20 to obtain a tert-butyl chloride solution; the tert-butyl chloride solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, after the addition is completed, the temperature is raised to room temperature, and the mixture is reacted at room temperature for 2 hours, dichloroethane and tetrahydrofuran are mixed in a mass ratio of 0.3:20 to obtain a dichloroethane solution, the dichloroethane solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, the reaction is continued for 1 hour after the addition is completed, and after the reaction is completed, the tetrahydrofuran is removed by vacuum rotary evaporation to obtain 1,2-bis(vinylphosphine)ethane;
[0050] (3) Chloro-terminated polylactic acid, 1,2-bis(vinylphosphine)ethane, potassium iodide, and dimethyl sulfoxide were mixed in a mass ratio of 1:9:0.5:30, reacted at 70°C for 8 hours, and after the reaction, pure water 4 times the volume of dimethyl sulfoxide was added for precipitation, filtered, and vacuum dried at 40°C for 24 hours to obtain pre-modified polylactic acid;
[0051] (4) Azobisisobutyronitrile, 4-mercaptophenylboric acid, and dimethyl sulfoxide were mixed in a mass ratio of 1:3:12, and pre-modified polylactic acid with a mass of 3 times that of azobisisobutyronitrile was added. Under nitrogen protection, the temperature was raised to 65° C. for reaction for 24 h. After cooling to room temperature, pure water with a volume of 4 times that of dimethyl sulfoxide was added for precipitation. The mixture was filtered and vacuum dried at 40° C. for 24 h to obtain modified polylactic acid.
[0052] (5) Trimethoxy (2-phenylethyl) silane and pure water were mixed in a mass ratio of 1:50, and the pH was adjusted to 4.5 with acetic acid. After stirring at 60°C for 15 minutes, 5 times the mass of trimethoxy (2-phenylethyl) silane was added to the halloysite nanotubes, and the stirring was continued for 2 hours. The mixture was filtered and washed with anhydrous ethanol for 4 times, and dried at 100°C to obtain pretreated halloysite nanotubes; 3,4-dihydroxybenzoic acid, pretreated halloysite nanotubes, anhydrous zinc chloride, phosphorus oxychloride, and cyclopentane were mixed in a mass ratio of 1:0.5:1.5:1.2:30, heated to 65°C, reacted for 2 hours, and pure water of an equal volume to cyclopentane was added and stirred for 5 minutes. Pure water of 30 times the volume of cyclopentane was continued to be added, stirred for 5 minutes, and then allowed to stand for 40 minutes. The mixture was filtered and washed with pure water for 3 times, and vacuum dried for 12 hours to obtain modified halloysite nanotubes;
[0053] (6) Weighing modified polylactic acid, modified halloysite nanotubes, and cellulose in a mass ratio of 1:0.05:0.3; mixing the modified polylactic acid, modified halloysite nanotubes, and cellulose, kneading them on an internal mixer at a temperature of 170° C. and a rotation speed of 30 rpm for 5 min, and then hot-rolling them on a press at a pressure of 10 MPa and a temperature of 180° C. for 10 min to obtain a biodegradable packaging material.
[0054] Comparative Example 1:
[0055] The preparation method of the degradable packaging material of Comparative Example 1 differs from that of Example 2 in that it does not contain steps (2) and (3), and step (1) is modified to mix lactic acid and 1,4-butanediol at a mass ratio of 1:0.001 at 0.096 MPa, heat to 125° C., distill for 3 h, add stannous octoate with a mass content of 0.8% of the mass of lactic acid, heat to 170° C., melt polycondense for 9 h, and after the reaction is completed, add 10 times the mass of chloroform of the lactic acid and stir for 10 min, then add anhydrous ethanol with a mass content of 4 times the mass of chloroform for precipitation, filter and vacuum dry at 40° C. for 24 h to obtain modified polylactic acid.
[0056] Comparative Example 2:
[0057] The preparation method of the degradable packaging material of Comparative Example 2 differs from that of Example 2 in that step (4) is not included, and step (3) is modified as follows: chlorine-terminated polylactic acid, 1,2-bis(vinylphosphine)ethane, potassium iodide, and dimethyl sulfoxide are mixed in a mass ratio of 1:8:0.4:25, reacted at 75°C for 9 hours, and after the reaction, pure water 4 times the volume of dimethyl sulfoxide is added for precipitation, filtered, and vacuum dried at 40°C for 24 hours to obtain modified polylactic acid.
[0058] Comparative Example 3:
[0059] The preparation method of the degradable packaging material of Comparative Example 3 differs from that of Example 2 in that step (5) is not included, and step (6) is modified as follows: modified polylactic acid, halloysite nanotubes, and cellulose are weighed in a mass ratio of 1:0.04:0.25; the modified polylactic acid, halloysite nanotubes, and cellulose are mixed, kneaded on an internal mixer at a temperature of 170°C and a rotation speed of 30 rpm for 7 minutes, and then hot-rolled on a press at a pressure of 10 MPa and a temperature of 180°C for 10 minutes to obtain a degradable packaging material.
[0060] Test Example 1:
[0061] Flame retardant performance test:
[0062] Test method: Test the limiting oxygen index of the sample according to standard GB / T 2406.2.2009. The results are shown in Table 1.
[0063] Table 1
[0064] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 31.0 Comparative Example 1 25.4 Example 2 31.4 Comparative Example 2 30.5 Example 3 31.5 Comparative Example 3 31.2
[0065] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the degradable packaging material prepared by the present invention has good flame retardant properties.
[0066] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that the hydroxy-terminated polylactic acid is reacted with 3-chloropropionyl chloride, then reacted with 1,2-bis(vinylphosphine)ethane, and finally reacted with 4-mercaptophenylboric acid to obtain the modified polylactic acid; the hydroxy-terminated polylactic acid reacts with the acyl chloride on 3-chloropropionyl chloride to obtain the chlorine-terminated polylactic acid, and 1,2-bis(vinylphosphine)ethane can introduce a flame-retardant phosphorus element into the polylactic acid to give the material good flame-retardant properties.
[0067] Test Example 2:
[0068] Antibacterial performance test:
[0069] Test method: The antibacterial performance of the degradable packaging materials prepared in the examples and comparative examples was tested using the shaking flask method according to the standard GB 15979-2002. The results are shown in Table 2.
[0070] Table 2
[0071] Antibacterial rate (%) Antibacterial rate (%) Example 1 95.86 Comparative Example 1 7.65 Example 2 96.32 Comparative Example 2 95.73 Example 3 96.25 Comparative Example 3 96.11
[0072] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the degradable packaging material prepared by the present invention has good antibacterial properties.
[0073] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that the hydroxy-terminated polylactic acid is reacted with 3-chloropropionyl chloride, then reacted with 1,2-bis(vinylphosphine)ethane, and finally reacted with 4-mercaptophenylboric acid to obtain the modified polylactic acid; the hydroxy-terminated polylactic acid reacts with the acyl chloride on 3-chloropropionyl chloride to obtain the chlorine-terminated polylactic acid, and the chlorine-terminated polylactic acid is extended by reacting with 1,2-bis(vinylphosphine)ethane to form a quaternary phosphonium salt, and the formation of the quaternary phosphonium salt can give the packaging material good antibacterial properties.
[0074] Test Example 3:
[0075] Mechanical properties test:
[0076] According to the standard of GB / T1040.2-2006, the packaging materials prepared in the examples and comparative examples were subjected to tensile performance tests on a tensile testing machine, with a gauge length of 20 mm and a tensile speed of 5 mm / min, and the tensile strength of the samples was recorded. The results are shown in Table 3.
[0077] Photodegradation performance test:
[0078] Test method: The degradable packaging materials prepared in the examples and comparative examples were placed in a UV light box. There were 4 Q-LabUVA340 UV lamps in the light box. The distance between the lamps was 10 cm. The distance between the sample and the lamp was 5 cm. The central wavelength of the UV light was 340 nm and the intensity was 13 mW / cm 2 The size of the light box is 130cm*45cm*20cm, and the irradiation time is 720h. After the irradiation, the tensile strength is tested according to the mechanical property test method and the tensile strength retention rate before and after ultraviolet irradiation is calculated. The results are shown in Table 3.
[0079] Table 3
[0080] Tensile strength(MPa) Tensile strength retention rate (%) Example 1 40.79 24.52 Example 2 40.96 24.71 Example 3 41.31 25.02 Comparative Example 1 30.27 26.36 Comparative Example 2 30.31 26.47 Comparative Example 3 35.49 86.53
[0081] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the degradable packaging material prepared by the present invention has good mechanical properties and degradability.
[0082] By comparison, the tensile strength of Examples 1 to 3 is greater than that of Comparative Examples 1 to 3, and the tensile strength retention rate of Examples 1 to 3 is less than that of Comparative Example 3, indicating that the modified halloysite nanotubes are prepared by reacting the halloysite nanotubes pretreated with trimethoxy (2-phenylethyl) silane with 3,4-dihydroxybenzoic acid, and the halloysite nanotubes as an inorganic filler can enhance the mechanical properties of polylactic acid, and the silane coupling agent trimethoxy (2-phenylethyl) silane is grafted on the surface of the halloysite nanotubes through the silanol group after hydrolysis, so that the surface of the halloysite nanotubes has phenyl groups, and the phenyl groups react with 3,4-dihydroxybenzoic acid to generate dihydroxybenzoic acid. The carbonyl group contained in the benzophenone structure and the dibenzophenone structure is a type of photosensitive group. After absorbing ultraviolet rays under sunlight, free radicals are generated, which promote the oxidation of the polylactic acid molecular chain, break it, and degrade it into low molecular weight compounds, thereby accelerating the degradation process of polylactic acid and increasing the degradation rate. The modified polylactic acid, modified halloysite nanotubes, and cellulose are mixed to prepare a degradable packaging material. The phenylboronic acid structure of the polylactic acid side chain, the phenolic hydroxyl structure on the surface of the modified halloysite nanotubes, and the polyphenolic hydroxyl structure on the cellulose can be cross-linked with phenylboronic acid at high temperature to generate a reversible borate ester structure. The formation of a cross-linked network can enhance the mechanical properties of the modified polylactic acid.
[0083] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A degradable packaging material, characterized in that: The degradable packaging material is prepared by mixing and hot-rolling modified polylactic acid, modified halloysite nanotubes and cellulose; The modified polylactic acid is prepared by reacting terminal hydroxyl polylactic acid with 3-chloropropionyl chloride, then with 1,2-bis(vinylphosphine)ethane, and finally with 4-mercaptophenylboronic acid. The modified halloysite nanotube is prepared by reacting the halloysite nanotube pretreated with trimethoxy(2-phenylethyl)silane and 3,4-dihydroxybenzoic acid.
2. A method for preparing a degradable packaging material, characterized in that: The method comprises the following preparation steps: (1) Under nitrogen protection, hydroxy-terminated polylactic acid and tetrahydrofuran are mixed in a mass ratio of 1:(20-30), and triethylamine in an amount of 4 times the mass of the hydroxy-terminated polylactic acid is added at 0°C, and then a 3-chloropropionyl chloride solution in an amount of 20 times the mass of the hydroxy-terminated polylactic acid is added dropwise at a rate of 1 mL / min. After the addition is completed, the mixture is stirred for 3-4 hours, the mixture is heated to room temperature, the reaction is continued for 12 hours, and the mixture is centrifuged at 5000 r / min for 30 minutes. The supernatant is taken, and the supernatant is added to n-hexane in an amount of 5 times the volume of tetrahydrofuran at -4°C for precipitation, and the mixture is filtered and vacuum dried at 40°C for 24 hours to obtain chlorine-terminated polylactic acid; (2) trivinyl phosphine and tetrahydrofuran are mixed in a mass ratio of 1:(5-6), stirred for 30-40 min under nitrogen protection, lithium in an amount of 0.05-0.07 times the mass of trivinyl phosphine is added, stirring is continued for 4-5 h, the temperature is lowered to 0° C., a tert-butyl chloride solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, after the addition is completed, the temperature is raised to room temperature, the mixture is reacted at room temperature for 2 h, and a dichloroethane solution in an amount of 20 times the mass of trivinyl phosphine is added dropwise at a rate of 1 mL / min, the reaction is continued for 1 h after the addition is completed, and after the reaction is completed, the tetrahydrofuran is removed by vacuum rotary evaporation to obtain 1,2-bis(vinylphosphine)ethane; (3) Chloro-terminated polylactic acid, 1,2-bis(vinylphosphine)ethane, potassium iodide, and dimethyl sulfoxide are mixed in a mass ratio of 1:(7-9):(0.3-0.5):(20-30), reacted at 70-80° C. for 8-10 h, and after the reaction, pure water 4 times the volume of dimethyl sulfoxide is added for precipitation, filtered, and vacuum dried at 40° C. for 24 h to obtain pre-modified polylactic acid; (4) Azobisisobutyronitrile, 4-mercaptophenylboric acid, and dimethyl sulfoxide are mixed in a mass ratio of 1:(2-3):(10-12), and pre-modified polylactic acid is added in an amount 2-3 times the mass of azobisisobutyronitrile. Under nitrogen protection, the temperature is raised to 65-70° C. for reaction for 24 h. After cooling to room temperature, pure water 4 times the volume of dimethyl sulfoxide is added for precipitation. The mixture is filtered and vacuum dried at 40° C. for 24 h to obtain modified polylactic acid. (5) 3,4-dihydroxybenzoic acid, pretreated halloysite nanotubes, anhydrous zinc chloride, phosphorus oxychloride, and sulfolane are mixed in a mass ratio of 1:(0.3-0.5):(1.3-1.5):(1.1-1.2):(20-30), heated to 65-70° C., reacted for 2-3 hours, added with pure water of an equal volume to the sulfolane, stirred for 5-10 minutes, continued to add pure water 30 times the volume of the sulfolane, stirred for 5-10 minutes, allowed to stand for 40 minutes, filtered, washed with pure water 3 times, and vacuum dried for 12 hours to obtain modified halloysite nanotubes; (6) The modified polylactic acid, the modified halloysite nanotubes and the cellulose were mixed, kneaded on an internal mixer at a temperature of 170° C. and a rotation speed of 30 rpm for 5-10 min, and then hot-rolled on a press at a pressure of 10 MPa and a temperature of 180° C. for 10 min to obtain a degradable packaging material.
3. The method for preparing a degradable packaging material according to claim 2, characterized in that: The preparation method of the terminal hydroxyl polylactic acid in step (1) is as follows: lactic acid and 1,4-butanediol are mixed at a mass ratio of 1:0.001 under 0.096 MPa, heated to 125° C., distilled for 3 hours, added with 0.8% of the mass of lactic acid stannous octoate, heated to 170° C., melt polycondensed for 9 hours, after the reaction is completed, added with 10 times the mass of lactic acid chloroform and stirred for 10 minutes, then added with 4 times the mass of chloroform anhydrous ethanol for precipitation, filtered and vacuum dried at 40° C. for 24 hours to obtain the terminal hydroxyl polylactic acid.
4. The method for preparing a degradable packaging material according to claim 2, characterized in that: The 3-chloropropionyl chloride solution in step (1) is prepared by mixing 3-chloropropionyl chloride and tetrahydrofuran in a mass ratio of 1:
5.
5. The method for preparing a degradable packaging material according to claim 2, characterized in that: The tert-butyl chloride solution in step (2) is prepared by mixing tert-butyl chloride and tetrahydrofuran in a mass ratio of (0.5-0.7):20; the dichloroethane solution is prepared by mixing dichloroethane and tetrahydrofuran in a mass ratio of (0.2-0.3):
20.
6. The method for preparing a degradable packaging material according to claim 2, characterized in that: The preparation method of the pretreated halloysite nanotubes in step (5) is as follows: trimethoxy (2-phenylethyl) silane and pure water are mixed in a mass ratio of 1:50, the pH is adjusted to 4.5-5.5 with acetic acid, and after stirring at 60° C. for 15 minutes, 5 times the mass of trimethoxy (2-phenylethyl) silane is added to the halloysite nanotubes, and stirring is continued for 2 hours. The mixture is filtered and washed with anhydrous ethanol for 4 times, and dried at 100° C. to obtain the pretreated halloysite nanotubes.
7. The method for preparing a degradable packaging material according to claim 2, characterized in that: In step (6), the mass ratio of the modified polylactic acid, the modified halloysite nanotubes and the cellulose is 1:(0.03-0.05):(0.2-0.3); the cellulose is corn straw cellulose powder with a particle size of 100 mesh.
8. The method for preparing a degradable packaging material according to claim 3, characterized in that: The lactic acid is L-lactic acid with a concentration of 88% and an optical rotation of ≥97%.
9. The method for preparing a degradable packaging material according to claim 6, characterized in that: The halloysite nanotube has a diameter of 30-50 nm and a length of 100-500 nm.
Citation Information
Cited By
Anti-aging biodegradable material and preparation method thereof
CN120590760A
Preparation method of antibacterial modified polylactic acid for packaging material
CN121182165A